Cross‐flow microfiltration for isolation, selective capture and release of liposarcoma extracellular vesicles. Issue 4 (16th February 2021) - Casadei, Lucia; Choudhury, Adarsh; Sarchet, Patricia; Mohana Sundaram, Prashanth; Lopez, Gonzalo; Braggio, Danielle; Balakirsky, Gita; Pollock, Raphael; Prakash, Shaurya
Abstract: We present a resource‐efficient approach to fabricate and operate a micro‐nanofluidic device that uses cross‐flow filtration to isolate and capture liposarcoma derived extracellular vesicles (EVs). The isolated extracellular vesicles were captured using EV‐specific protein markers to obtain vesicle enriched media, which was then eluted for further analysis. Therefore, the micro‐nanofluidic device integrates the unit operations of size‐based separation with CD63 antibody immunoaffinity‐based capture of extracellular vesicles in the same device to evaluate EV‐cargo content for liposarcoma. The eluted media collected showed ∼76% extracellular vesicle recovery from the liposarcoma cell conditioned media and ∼32% extracellular vesicle recovery from dedifferentiated liposarcoma patient serum when compared against state‐of‐art extracellular vesicle isolation and subsequent quantification by ultracentrifugation. The results reported here also show a five‐fold increase in amount of critical liposarcoma‐relevant extracellular vesicle cargo obtained in 30 min presenting a significant advance over existing state‐of‐art.